Usage of Green Material in Building Construction Evaluating its Outcome on Varied Properties of Concrete - Muzamil Yaqoob; Shoaib Salim; Muhammad Ali; Mian Muhammad Wasim; Zia Ullah; Shahzad Khalil (Journal of ICT, Design, Engineering and Technological Science, 2021)
Rice Husk Ash was selected as a green material. Two types of Rice Husk Ash (RHA) were considered and one of them was selected for this study. The RHA was characterized and its effect on the properties of cement, especially strength and shrinkage were studied. Four formulations containing 0, 10, 15 and 20 percent of RHA were prepared for flexure, compression and shrinkage including X-ray diffraction and fluorescence test. All formulations were prepared at their standard consistency. The results indicated that the RHA used in our study was not an effective pozzolanic material and had an adverse effect on the strength and shrinkage properties of the cement formulations due to its increased water demand and large particle size. This investigation proved that it cannot be used in the projects where early higher strength is needed.